Guest

Subtract: –m2 + 5mn from 4m2 – 3mn + 8 Subtract: –m2 + 5mn from 4m2 – 3mn + 8

Subtract:
–m2 + 5mn from 4m2 – 3mn + 8
Subtract:
–m2 + 5mn from 4m2 – 3mn + 8

Grade:12

1 Answers

Harshit Singh
askIITians Faculty 5963 Points
2 years ago
Dear Student

When term have the same algebraic factors, they are like terms.
Then, we have to subtract the like terms
= 4m^2–3mn + 8–(- m^2+ 5mn)
= 4m^2–3mn + 8 + m^2- 5mn
= 4m^2+ m^2–3mn - 5mn + 8
= 3m^2- 8mn + 8

​Thanks

Think You Can Provide A Better Answer ?